Access to rehabilitation after stroke in Brazil (AReA study): multicenter study protocol - de Oliveira Cacho, Roberta (2022)
Background Most of the Brazilian population relies on public healthcare and stroke is a major cause of disability in this country of continental dimensions. There is limited information about access to rehabilitation after stroke in Brazil. Objective To provide comprehensive information about Access to Rehabilitation After discharge from public hospitals in Brazil (AReA study), up to 6 months after stroke. Methods The present study intends to collect information from 17 public health centers in 16 Brazilian cities in the 5 macroregions of the country. Each center will include 36 participants (n ¼ 612). The inclusion criteria are: age ≥ 18 years old; ischemic or hemorrhagic stroke, from 6 months to 1 year prior to the interview; admission to a public hospital in the acute phase after stroke; any neurological impairment poststroke; patient or caregiver able to provide informed consent and answer the survey. Patients can only be recruited in public neurology or internal medicine outpatient clinics. Outcomes will be assessed by a standard questionnaire about rehabilitation referrals, the rehabilitation program (current status, duration in months, number of sessions per week) and instructions received. In addition, patients will be asked about preferences for locations of rehabilitation (hospitals, clinics, or at home). Trial Status The study is ongoing. Recruitment started on January 31st, 2020 and is planned to continue until June 2022. Conclusion The AReA study will fill a gap in knowledge about access to stroke rehabilitation in the public health system in different Brazilian regions.